Immunohistochemical analysis of IDH1, ATRX, p53, and Ki-67 in glioblastoma and diffuse infiltrative glioma: therapeutic and prognostic correlation - Hasbay, Bermal; Kayaselçuk, Fazilet; Suner, Halil İbrahim and Tufan, Kadir (Vojnosanitetski pregled, 2025)
Background/Aim. The most common molecular alterations in high-grade astrocytoma include mutation of the isocitrate dehydrogenase (IDH) gene, loss of 1p19q, and p53 mutation. The aim of the study was to determine the prevalence of high-grade astrocytoma and glioblastoma and to examine the immunohistochemical staining patterns of IDH1, alpha-thalassemia/mental retardation X-linked (ATRX), p53, and Ki-67, as well as neoplastic morphological findings, treatment response, and effects on prognosis. Methods. Patients with IDH-mutant or IDH-wild-type glial tumors diagnosed at our center between January 2016 and January 2022 were included in the study. Patients were divided into groups according to age as follows: 7–40, 41–55, 56–64, and ≥ 65 years. The impact of demographic and clinical features on survival was analyzed. The effects of IDH1, p53, ATRX, and Ki-67 parameters on treatment success and prognosis were investigated. The Chi-square test was used to compare independent categorical variables, while the McNemar test was used for dependent categorical variables between the groups. Kaplan-Meier method and Cox proportional regression model (forward model) were used to estimate the mean and median survival times, failure rates, and hazard ratios. Results. In the study, 115 (56.1%) patients were male and 90 (43.9%) were female. The patients ranged in age from 7 to 84 years. There was no significant relationship between gender and age groups on survival (p = 0.113). However, there was a significant association between the glioblastoma grade and survival (p = 0.024). There were 65 (31.7%) patients who died. The mean overall survival of all patients was 45.2 months (median: 24 months). While 45 (21.2%) patients were found to have IDH1 mutation, the number of patients negative for the mutation was 160 (78.8%). Overall survival was significantly longer in IDH1-positive patients (mean: 65.8, median: 80) than in IDH1-negative patients (mean: 25.7, median: 22) (p = 0.019). Conclusion. It was found that mutations of IDH1 and ATRX and overexpression of p53 alone significantly impacted the prognosis of glioblastoma patients. However, radiotherapy and chemotherapy had a positive effect on patient survival. Survival can be increased by adding additional treatments to patients with ATRX mutations.